The Influence of Reflective Learning Model on Students' Metacognitive Awareness in Islamic Religious Education - Qosim, Muhammad Nanang; Misnawati, Desy; Elihami, Elihami; Musa, Muhajir; Saputra, Nanda (Jurnal Ilmu Pendidikan, 2023)
This study aims to explore how implementing a reflective learning model affects students' metacognitive awareness in the context of Islamic Religious Education. A single-group pretest-posttest experimental design was employed, involving 62 participants divided into experimental and control groups. Data were gathered using a metacognitive awareness questionnaire comprising 20 items. The findings from the t-test analysis with a significance level of 0.001 revealed a significant disparity in metacognitive awareness between the experimental and control groups. The experimental group, which utilized the reflective learning model, exhibited a considerably more significant enhancement in metacognitive awareness compared to the control group that employed a traditional learning model. These suggest that using a reflective learning model positively influences students' metacognitive awareness in the context of Islamic Religious Education. The implications of this research emphasize the necessity of integrating reflective learning models into the teaching practices of Islamic Religious Education to promote students' metacognitive awareness